Late maturers at a performance disadvantage to their more mature peers in junior Australian football - Gastin, P. B.; Bennett, G. (Journal of Sports Sciences, 2014)
Children and adolescents mature at different rates such that individuals competing in the same competition may differ in physical and biological maturity despite being of similar chronological age. Whether or not differences translate into on-field performance in competition is relatively unknown. This study investigated the influence of biological maturity on fitness and match running performance in junior Australian football. Eighty-seven under-15 years players were categorised into early (n = 20), average (n = 45) and late (n = 22) maturity groups based on self-reported and anthropometric assessment of biological maturity. Running movements during competition were collected using GPS (5 Hz) technology. Early maturers were heavier and taller than all other boys (P < 0.05), while biological maturity was significantly correlated to 20 m sprint (r = 0.53, P < 0.01). Total distance, high-intensity (>14.4 km/h) running distance and number of high-intensity efforts were significantly greater (20.8%, 53.6%, 31.7%, respectively; P < 0.01) in early compared to late maturers. Number of sprints and peak speed in competition were not different. Pubertal development and maturity status partially explained the differences between players in physical size, functional running fitness and match running performance. Late maturing players in this Australian football under-15 age group were at a physical and performance disadvantage to their earlier maturing peers.